«Joumal du dehors» et «La vie extérieure» d'Annie Ernaux: l'engagement au quotidien - Thiel-Jańczuk, Katarzyna (Wydawnictwo Naukowe UAM, 2003)
The article «"Journal du dehors» et «La vie extérieure» d'Annie Ernaux: l'engagement au quotidien" is an analysis of Ernaux's two texts within P. Bourdieu's sociological perspective. Taking an observation of the surrounding reality, where the narrative "I" is situated, as a starting point, Ernaux distinguishes two types of everyday situations: rituals and individual activities. The former shape mass behaviour which is governed by the political and economic system, whereas the latter - labelled by M. de Certeau as «pratiques subversives» - subconsciously go beyond the norm-established behaviour. Both types belong to popular culture and concern people who are dominated (domines). Taking their side, both word and deed, Ernaux defies the conventional structures she is entangled in by the mere fact of being a writer. Ernaux expresses this defiance in two ways. First, by rejecting the elitist notion of creator, second, through abandoning memory as a source of writing, by resigning from the genre of novel in favour of texts which deal with the synchronic movement of the narrative "I" in the world.
Journal du dehors and La vie exterieure of Annie Ernaux: A Daily Life Involvement
Keywords: Ernaux, Annie; Sociological perspective